2012
DOI: 10.1111/j.1539-6924.2012.01832.x
|View full text |Cite
|
Sign up to set email alerts
|

Flood Risk Management: US Army Corps of Engineers and Layperson Perceptions

Abstract: Recent severe storm experiences in the U.S. Gulf Coast illustrate the importance of an integrated approach to flood preparedness planning that harmonizes stakeholder and agency efforts. Risk management decisions that are informed by and address decision maker and stakeholder risk perceptions and behavior are essential for effective risk management policy. A literature review and two expert models/mental models studies were undertaken to identify areas of importance in the flood risk management process for layp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 48 publications
0
45
0
Order By: Relevance
“…Given that flooding is often widespread, uncontrollable and devastating, it is indeed normal for communities to look up to Governments who often have the leverage to provide the kind of assistance needed. For instance, Wood et al [7] has noted that, even in developed economies such as the US where there is relatively high awareness and involvement of communities, many communities still expect the government to take the full burden of flood risk management, including those effecting their personal loss and liability. However, it is also now known that societal drivers in terms of social responsibility and willingness to prepare for an event and knowing how to prepare is also crucial in building CS to flood hazards [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that flooding is often widespread, uncontrollable and devastating, it is indeed normal for communities to look up to Governments who often have the leverage to provide the kind of assistance needed. For instance, Wood et al [7] has noted that, even in developed economies such as the US where there is relatively high awareness and involvement of communities, many communities still expect the government to take the full burden of flood risk management, including those effecting their personal loss and liability. However, it is also now known that societal drivers in terms of social responsibility and willingness to prepare for an event and knowing how to prepare is also crucial in building CS to flood hazards [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed that even though the two communities are not oblivious of the fact that, their communities are high risk, they lack any systematic effort in taking the initiative to contribute in developing their adaptive capacity to help manage floods. Emerging issues suggest that it will need a lot of deep understanding of community perceptions, actions and behaviours for them to be convinced in living to their social responsibility [7]. The decentralization concept in Ghana allows for the election of local representatives of community members called Assemblymen and their Unit committee members.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these research findings often do not significantly influence the practitioner flood risk community. This is due to the difference in the perception of flood risks between model developers and flood risk practitioners [11][12][13][14]. The researchers generally frame flood risk issues using scientific knowledge and expertise.…”
Section: Introductionmentioning
confidence: 99%